3D self-supported FeOP film on nickel foam as a highly active bifunctional electrocatalyst for urea-assisted overall water splitting. (April 2018) - Li, Yuanjian; Wang, Huanwen; Wang, Rui; He, Beibei; Gong, Yansheng
Graphical abstract: The FeOP film was directly deposited on the Ni foam by the atom layer deposition technique and the subsequent phosphonation process for urea-based overall water splitting. Highlights: ALD FeOx is firstly used to synthesize the amorphous FeOP composite. The urea oxidation (UOR) is used for Ienergy-intensive hydrogen production. Highly porous carbon layer is tightly connected with conductive graphene sheets. High UOR activity with a low potential of 1.34 V (vs. RHE) at 10 mA cm −2 . The superior bifunctional activity of the FeOP/NF for water-splitting. Abstract: Replacement of oxygen evolution (OER) by the more readily oxidized urea is considered to be a promising strategy for electrocatalytic water-splitting. In this work, we report a FeOP film on nickel foam (FeOP/NF) via atomic layer deposition (ALD) of iron oxide and a subsequent phosphonation process, which acts as a superior bifunctional electrocatalyst for both urea evolution reaction (UOR) and hydrogen evolution reaction (HER). Benefiting from the synergetic effects, the FeOP/NF exhibits a low potential of 1.34 V (vs. RHE) at 10 mA cm −2 and a low Tafel slope of 57.2 mV dec −1 for UOR. Combined with the high HER activity of FeOP/NF, the urea-based overall water splitting can be performed with an low voltage of 1.43 V to deliver 10 mA cm −2 in 1.0 M KOH with 0.5 M urea, which is 200 mV lower than that for pure water splitting.